DO AUTONOMY SUPPORTS IMPROVE MEDICAL STUDENTS’ MOTIVATION IN A DEVELOPING COUNTRY? - Elizabeth Sulastri Nugraheni; Doni Widyandana; Rachmadya Nur Hidayah (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2022)
Background: Medical students in private schools are mostly high school graduates, ages are around 17 to 18. They were so diverse, the background of the former school, culture, motivation, and study skills. Students from rural might have different motivation and study skills from students of big cities. To give autonomy support to the new medical students, we planned the motivational workshop and study skills mentoring. We assume those will increase their motivation.Aims: To know - What types of motivation do first-year medical students have? Secondly, to evaluate - Whether motivational workshops and mentoring about study strategies can help to increase students’ autonomous motivation based on the Self-Determination Theory.Methods: A mixed-methods research was conducted in this study. The first step was the quantitative study using the Academic Motivation Scale (AMS) to measure the students’ pre and post intervention motivation and the Intrinsic Motivation Inventory (IMI) post intervention, then followed by the qualitative study to capture students’ responses and reflections with convenience sample.Results: The autonomous motivation was high among the male students, home-schooling, does not belong to medical profession family, and students from lower middle income. Quantitative data showed that this approach significantly decreased the amotivation scale of participants (p=0.025). Descriptively, there was an increase in the autonomous motivation of participants after following motivational workshop and study strategies mentoring.Conclusion: Motivational workshops and mentoring on study strategies were found to be valuable, interesting, and facilitate autonomous motivation. Results showed that those activities increased the students’ autonomous motivation.